Experimental and simulation study on the effect of friction in a Four-Point Bending Test (4PB) - Abdul Zarif, Abdul Malek (2012)
Finite element evaluation is one of the methods in predicting the strain value in sheet metal bending. Predicting the strain value is sometimes used in areas of plastic deformation, which is the integral of the ratio of the incremental change in length to the instantaneous length of a plastically deformed. This thesis aims to evaluate the reliability of finite element method by comparing the results with experimental results. The effect of parameters such as length of displacement after bend also has been studied. Abaqus software has been used to simulate the bending process and the mechanical properties provided from the Solidwork data will be used to run the simulation. In the four-point bending experiment, the test rig was clamped on Shimadzu machine and the mild steel sheets was assembled with strain gauge before bend process was run. Strain value being measured with Dasylab software. The results from the experiment and simulation is slightly different for value of strain, which the simulation shows the value of strain higher than strain value that was get from the experiment. For the free force four-point bending, value length displacement after bend almost the same on the simulation and experimental. Finite element method can be used to make comparison since the pattern of the graphs are nearly the same and percentages of error are below 10 %. The further study on parameters that effected bending process will make the finite element method is important in the future.